The Contemporary Martial Arts Master-Teacher as a Complete Warrior - Wojciech J. Cynarski (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Background. Learning martial arts, even the Japanese budō tradition, can be limited to a single discipline. But for comprehensiveness, it is possible to study a whole range of disciplines. Problem. What characterizes a master-teacher who has mastered various martial arts? What distinguishes the master we call a complete warrior? Method. Ten renowned masters of the highest rank who achieved high ranks and titles in various martial arts disciplines were considered. A comprehensive index measurement and qualitative analysis were used. Knowledge derived from direct acquaintance with the author, who has been active in the martial arts community for many years (48 years of participant observation), as well as data from the literature on the subject were used. Results and Conclusions As a complete warrior, the master-teacher possesses skills in wielding various weapons, not just saber fencing. He also possesses proven hand-to-hand combat skills, both at a distance and in close combat. In each case, these were decades of daily or regular practice—practical study.